A COMPARATIVE ANALYSIS OF TRADITIONAL AND ONLINE TEACHING METHODS FOR STUDENT SUCCESS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
One of the important necessities of today’s world is learning foreign languages. For teaching these languages there are different methods including traditional and online teaching that differ from each other. Students have diverse learning preferences. Some thrive in traditional classroom settings, while others find online learning more engaging and effective. Comparative analysis canhelp educators identify which methods best suit different learning styles and needs. This article delves into the differences of these two methods and their effectiveness for students’ success